Changes in severity of influenza A(H1N1)pdm09 infection from pandemic to first postpandemic season, Germany - Giesen, Nicola; Geis, Steffen; Eisenbach, Christoph; Neben, Kai; Schnitzler, Paul (Emerging infectious diseases, 2013)
We studied risk factors for a severe clinical outcome in hospitalized patients with laboratory-confirmed influenza A(H1N1)pdm09 infection at the University Hospital Heidelberg in the pandemic and first postpandemic seasons. We identified 102 patients in 2009–10 and 76 in 2010–11. The proportion of severely diseased patients dramatically increased from 14% in 2009–10 to 46% in 2010–11 as did the mortality rate (5%–12%). Patients in the first postpandemic season were significantly older (38 vs. 18 years) and more frequently had underlying medical conditions (75% vs. 51%). Overall, 50 patients (28%) had a severe clinical outcome, resulting in 14 deaths. Multivariate analysis showed that older male patients with chronic lung disease were at increased risk for a severe clinical outcome. In summary, the proportion of patients with severe disease and fatal cases increased in the postpandemic season. Therefore, patients with suspected infections should be promptly identified and receive early treatment.
Gesehen am 15.12.2021
Im Artikel ist die URL zum Klartext falsch angegeben, DOI: http://dx.doi.org/10.3201/eid1905.120034